Efeitos de uma intervenção em comunicação aumentativa e alternativa para crianças com necessidades complexas de comunicação - Gomes, Maria Caroline Volpin (Universidade Federal de São Carlos, 2026)
The absence or difficulty of communication during childhood causes impacts on development, the acquisition of autonomy, and the performance of roles in areas of occupation that are typical of this stage. Augmentative and Alternative Communication (AAC) aims to compensate for difficulties and/or disabilities that are expressed temporarily or permanently by individuals who present deficits in expression or comprehension. From this perspective, the occupational therapist, in partnership with special education professionals, can establish collaborative work in order to ensure access to communication and guarantee the full exercise of human rights for individuals with complex communication needs (CCN). Thus, this study was characterized as a single-subject research design of the AB Follow-up type, with the objective of verifying the effects of an intervention focused on AAC in the occupational therapy clinical setting. Two children with CCN participated in the intervention—one diagnosed with cerebral palsy and the other with autism spectrum disorder—aged nine and five years, respectively, and indirectly, their mothers and teachers. The procedures involved the application of instruments for the selection, assessment, and characterization of the children, the implementation of weekly therapy sessions, the recording of these sessions, guidance provided to teachers, and social validation with the mothers and teacher. Based on the independent variable (AAC intervention) and the dependent variable (the child’s communicative function), data were analyzed descriptively, both qualitatively and quantitatively, organized into tables and quantified by frequency of occurrence of opportunities and responses. As results, it was observed that both participants showed an increase in response emissions after phase B and an increase in the percentage of communicative types. One participant progressed from communicative intent to the use of conventional gestures and the use of a symbol through eye gaze, while the other progressed from communicative intent to the use of two or more symbols on a robust high-technology communication board. Regarding social validation, the mothers and teacher reported perceiving improvements in the participants’ interactions. It was concluded that the proposed interventions produced positive effects on the participants’ communication, as both began in phase A as emerging communicators and, at follow-up, were classified as a transitional emerging communicator and a context-dependent communicator. The findings of this study highlight that interventions tailored to the demands, interests, and life context of each AAC user are essential for the effectiveness of system use, ensuring that it is not only available but truly functional for communication.
Effects of an augmentative and alternative communication intervention for children with complex communication needs
Keywords: Educação especial; Comunicação alternativa; Intervenção; Terapia ocupacional; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade